The Responses of Non-English Major Students with Visual Learning Style of Writing Towards Oral English Test - Sari, Angela Bayu Pertama (Universitas Ahmad Dahlan, 2018)
This research is conducted towards the students of non-English major with visual learning style and writing preference. There are 14 students, which are taken to be the respondents. Questionnaires are the instrument used to gather the data in this research. This research employs descriptive qualitative method in analyzing the data. The result portrays that 3 major findings: (1) most of the students find it difficult to accomplish the oral English test which is natural and normal due to their preference skill in writing, (2) in spite of the difficulty of the oral English test, the majority of the students consider the test to be challenging, accommodating and satisfying (3) a large number of the students get the benefit from the effectiveness of the feedback that they get in the form of rubrics.